'The First Rip Off': anti-circumcision activism in men's magazines. Issue 3 (3rd July 2018) - Allan, Jonathan A.
ABSTRACT: This article explores the rise of 'intactivism', a social movement which positions itself as being against circumcision, in the pages of Hustler magazine. Intactivism has largely been studied in terms of letters to the editor of newspapers and online engagement, but in this article I explore pornography. Drawing on archival research, this article considers articles published in Hustler in the 1970s, as well as the letters that were submitted to Hustler about the articles. As such, this article broadens the scope of analysis for scholars of anti-circumcision to include the pornographic, about which very little has been written.